2019
DOI: 10.3390/buildings9020038
|View full text |Cite
|
Sign up to set email alerts
|

Performance Review of Prefabricated Building Systems and Future Research in Australia

Abstract: Volumetric prefabricated building construction is growing in most developed countries; for example, in Sweden the market share of prefabricated building systems in the housing industry was more than 80%. However, in Australia only approximately 3–4% of new building constructions are prefabricated buildings in a year. A major hindrance to the growth of prefab construction in Australia is that systems are developed under commercial and confidential conditions. There are limited publicly-available research and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(122 citation statements)
references
References 36 publications
4
117
0
1
Order By: Relevance
“…Lu and Yuan [47] indicated that transportation cost can increase to over 18 per cent of the total cost, taking into account the long-distance transport due to offshore manufacture. Apart from that, weight and dimensions of modules is another constraint, which not only restricts the transportation route but also elevates the expenditure resulting from the specific requirement for vehicles [48,49]. Regardless of which methods of transport are utilised, cargo, rail or road, the damage to modules during the transit is not to be neglected.…”
Section: Related Workmentioning
confidence: 99%
“…Lu and Yuan [47] indicated that transportation cost can increase to over 18 per cent of the total cost, taking into account the long-distance transport due to offshore manufacture. Apart from that, weight and dimensions of modules is another constraint, which not only restricts the transportation route but also elevates the expenditure resulting from the specific requirement for vehicles [48,49]. Regardless of which methods of transport are utilised, cargo, rail or road, the damage to modules during the transit is not to be neglected.…”
Section: Related Workmentioning
confidence: 99%
“…They have shown concerns that it is not sustainable to purely rely on the governmental policies if there is a lack of real cases to demonstrate such benefits to the industry, especially to the client and end users. This is also the case for engineers and regulators [48]. A recent review article also highlighted the lack of evidence that the life cycle performance of prefabricated buildings is better than conventional buildings [49].…”
Section: Operational Stagementioning
confidence: 99%
“…As highlighted above, one of the essential marketing strategies for SIPs focuses on its environmental performance. Offsite manufacturing has been widely reported as one of the significant ways to reduce the amount of waste [6,16,27] for which the built environment is responsible [28,29]. Thus, SIPs, offering the same method to manufacture the structural components [5], is no exception.…”
Section: Buildermentioning
confidence: 99%